1984
DOI: 10.1149/1.2115953
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion of Carbon Black Anodes in Alkaline Electrolyte: I . Acetylene Black and the Effect of Cobalt Catalyzation

Abstract: 14 c labeling of acetylene black was used together with mass spectroscopic analysis of the gas evolved to determine the current efficiencies for oxygen evolution, carbon dissolution, and carbon gasification (to carbon monoxide}. The current efficiencies were found to depend dramatically on potential, temperature and the presence of an evolution catalyst like Co 3 o 4 . On uncatalyzed black, three regimes could be distinguished: I. -at potentials below 500 mV vs. Hg/HgO and temperatures below 50°C, carbon disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
6

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 12 publications
1
56
0
6
Order By: Relevance
“…It was further submitted to cyclic polarisation at 100 mV s À1 up to a stationary profile, taking its ocp as the lower limit. The upper limits were 0.36 and 0.45 V for 1.0 and 6.0 M KOH, respectively, to avoid carbon oxidation in such media [24]. Pure H 2 was then injected into the anode to reach the corresponding equilibrium potential and afterwards, positive linear sweep voltammograms starting at this potential were recorded at 1 mV s À1 with ohmic drop correction.…”
Section: Methodsmentioning
confidence: 99%
“…It was further submitted to cyclic polarisation at 100 mV s À1 up to a stationary profile, taking its ocp as the lower limit. The upper limits were 0.36 and 0.45 V for 1.0 and 6.0 M KOH, respectively, to avoid carbon oxidation in such media [24]. Pure H 2 was then injected into the anode to reach the corresponding equilibrium potential and afterwards, positive linear sweep voltammograms starting at this potential were recorded at 1 mV s À1 with ohmic drop correction.…”
Section: Methodsmentioning
confidence: 99%
“…Cyclic voltammograms (CVs) were recorded in a 1 M KOH solution between À0. 2 [11] composite electrodes. The last value was obtained considering that Vulcan XC72R and spinel oxide, which possess different reference capacitances, are both electroactive in the potential range investigated in this work.…”
Section: Electrochemical Characterizationsmentioning
confidence: 99%
“…Also, it has been well demonstrated that whereas the current efficiency for oxygen evolution of a cobalt oxide-catalyzed acetylene black electrode is increased severalfold relative to that for the uncatalyzed black sample, the rates of the corrosion processes are also accelerated [2,3]. Therefore, the development of a more anodically stable catalyst support is mandatory for rechargeable metal-air batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, the kinetically slow but thermodynam-ically favoured carbon oxidation into carbonate during battery operation can proceed [4]. Ross and Sokol [5] studied this corrosion process in alkaline solutions using 14 C labelling technique, and found that oxidative carbon dissolution and gasification (to carbon monoxide) occurred at different temperatures and applied potentials. Impedance analysis of rechargeable metal-air batteries also showed that electrode deterioration during anodic oxygen evolution was mainly due to carbon corrosion, resulting in a loss in electrochemical active surface area [1].…”
Section: Introductionmentioning
confidence: 99%